Launching of the Bio-resources Innovation Network for Eastern Africa Development (Bio-Innovate) Program hosted at ILRI-Nairobi - International Livestock Research Institute (International Livestock Research Institute, 2011)
Bio-resources Innovation Network for Eastern Africa Development (Bio-Innovate) Program, which is hosted by the International Livestock Research Institute (ILRI) began in January 2010 with support from the Swedish International Development Agency (Sida). ;This five-year program is investing USD12 million in funding about a hundred scientists and policymakers from Burundi, Ethiopia, Kenya, Rwanda, Tanzania and Uganda.